Use of a webcam for movement detection - Silva, W. R. S.; Pereti, N. C.; Rogeri, J. G.; Pereira, A. S. [UNESP]; Marranghello, N. [UNESP]; Araujo, A. F.; Tavares, Joao Manuel R. S.; Tavares, JMRS; Jorge, RMN (Crc Press-taylor & Francis Group, 2014)
Accessibility evolving as a major concern nowadays, the suppression the utilization of a mouse while the user interacts via an interface becomes relevant as well. The work described herein aims at creating a method to control a computer through a webcam, which recognizes the movements of the user hands and moves the cursor accordingly. The proposed method turns out to be reliable and presents a low computational cost being capable of fulfilling the requirements of several applications.